PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VII MTSN PASIR LAWAS - Darwis, Afifah; Maris, Ika Metiza; Zulmardi, Zulmardi (Jurnal Pembelajaran MIPA, 2014)
The purpose of this reseach is to know that understanding of student mathematics concept with applying Student Facilitator and Explaining model is better than conventional study. This is a quasi-experimental study, the design of Randomized Control Group Only Design. Research procedures can be divided into three phases: preparation, conduct implementation and completion. Research instrument used was test students understanding of math concepts. Test instrument was developed by compiling test, validation test questions, test and analysis of test items. Analysis using t-test. Results of this study showed an increase in students understanding of mathematical concepts, differences in average value, standard deviation and variance between the experimental class and the control class.Key words: models of student facilitator learning and explaining, the ability of understanding mathematical concepts